Self-referenced refractive index sensing with hybrid-Tamm-plasmon-polariton modes in sub-wavelength analyte layers. (24th August 2017) - Kumar, Samir; Shukla, Mukesh Kumar; Maji, Partha Sona; Das, Ritwick
Abstract: A coupled Tamm-plasmon-polariton (TPP) hybrid-mode based self-referenced refractive-index sensor is proposed. The geometry is comprised of a sub-wavelength analyte (sensing) layer sandwiched between two metal-clad distributed-Bragg-reflectors (DBRs). Reflection spectrum of the geometry exhibits two discernible reflectivity minima within the photonic-bandgap of DBR. The reflectivity minima are essentially due to excitation of two hybrid modes which have symmetric and anti-symmetric field distribution about the center resulting in an anti-crossing behaviour exhibited by hybrid-TPP mode dispersion curves. The low frequency symmetric mode exhibits strong dispersive properties by virtue of significant presence of mode-field in sensing medium. On the other hand, the high-frequency anti-symmetric mode remains unchanged with alterations in sensing layer. Thus, we propose a self-referenced sensing scheme using hybrid-TPP modes with sensitivity varying from 65   n m   R I U − 1 to 180   n m   R I U − 1 in the visible band. In addition, the TPP resonance are appreciably sharp as compared to surface-plasmon based geometries which results in improved detection accuracy and figure of merit. We also present an analysis for optimizing the sensor design for enhancing the sensitivity as well as detection accuracy.